L’assurance de responsabilité civile complémentaire des entreprises - Moreau, Rémi (Assurances, 1989)
Today, corporations can more easily protect themselves from the dangers of jumbo claims than three years ago, and insurers are writing umbrella liability insurance policies which have less stringent terms and conditions. This type of policy is one of the most important an insured can purchase. It provides coverage for catastrophic liability losses because of its high limits. In fact, the three basic functions of an umbrella policy are: to extend the limits of the primary liability policies, to replace primary coverage once the primary aggregate limits have been exhausted, and to afford broader coverage than primary policies provide, subject to a retention amount. The author provides an overview of the structure of an umbrella policy including insuring agreements, conditions, and exclusions.